If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 12 = 10x + 9 Reorder the terms: 12 + 7x = 10x + 9 Reorder the terms: 12 + 7x = 9 + 10x Solving 12 + 7x = 9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + 7x + -10x = 9 + 10x + -10x Combine like terms: 7x + -10x = -3x 12 + -3x = 9 + 10x + -10x Combine like terms: 10x + -10x = 0 12 + -3x = 9 + 0 12 + -3x = 9 Add '-12' to each side of the equation. 12 + -12 + -3x = 9 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 9 + -12 -3x = 9 + -12 Combine like terms: 9 + -12 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 4n+3=n-7 | | 234/3*x-30=906 | | 130*5/x+90=415 | | -6-4=9x+3-8x | | x/3+50=250 | | 60*15/x=100 | | 97+673-x=737 | | -24+4x=6-6(5+5x) | | 3-5x=21 | | 22*x=286 | | 3+5x=21 | | -5-3x=-32 | | (5x+10y+4)2= | | 23-4x=8 | | -2(-1+4n)=-7+n | | 4x^2-14=4x | | 4+8x=23 | | 4+18x=23 | | 23-8x=14 | | f(x)f(y)-xy=f(x)+f(y)-1 | | 23-14x=18 | | 4k^2-6=-21 | | X*1.4=10 | | 5(2x+12)+6(x+20)= | | -1+5(6x-1)=6x-30 | | 8+5x=30 | | 8+4x=30 | | x-3=-28 | | 2x^3+3x^2+120x=0 | | 30+14x=8 | | 30-14x=8 | | x-0.15x=200 |